Aplasia of the vagina and uterus (Mayer-Rokitansky-Kustner-Hauser syndrome): etiology, pathogenetic aspects and theory of the formation of defect (literature review) - D.A.Kruglyak; N.A.Buralkina; M.V.Ipatova; Z.K.Batyrova; E.V.Uvarova (IP Berlin A.V., 2018)
The article provides data on the etiology and pathogenesis of genital malformation - vaginal and uterine aplasia (Mayer-Rokitansky-Kustner-Hauser syndrome) at the present stage.